The Nexus between Instructional Supervision, Supervisors’ and Teachers’: The Practical Paradox and Its Effect on Quality Education a case of Woliat Zone Administration Elementary and Secondary Schools (1-8) - Dea, Mulatu (IJRDO- Journal of Educational Research, 2016)
Even though the new instructional supervision practices materialized in the schools level, teacherswere not properly supported well, so that the students achievements was decreasing in nationalexams than before as the regional grade report documents revealed and quality is deterioratingfrom time to times. Hence, the main objective of this study is explore the practice of instructionalsupervision and interaction of teachers and supervisors at Wolaita zone Administrationelementary and secondary schools and to see the nexus between the practices and qualityeducation. Cross sectional survey type research design were instrumental. The research approachwas quantitative dominant qualitative. Questionnaire (5 Likert scale items), Key informantinterview and document analysis were employed as data collection instruments. To check internalconsistency reliability Cronbach’s Alpha with value of r=0.852. The schools were selected throughcluster sampling technique; availability sampling for woreda supervision head and clustersupervisors’, moreover purposive sampling technique for school leaders. Simple random samplingwas employed to select the teachers’. Based on this technique, a total of 229 respondents weretaken and the sample size determination focuses on 95 % confidence level and within 5 % confidentlimit. One way ANOVA were used to see the variations between and within groups by consideringits assumptions. Moreover, binary logistic regression model adopted to determine the relationshipbetween a binary dependent variable and a set of independent variables at Beta label (β). Chisquaredtest were also used to see the relationship between two categorical variables. From thestudy it is possible to conclude that, even though the instructional supervision require cooperativework, the sample schools were not found to be working mutually and the practice also lacksregular and continuous support to teachers in the ways to improve teaching learning methods andimproving students’ performance, lacks appropriate guidelines and resources and no standardizeddata collection instrument to collect information at the time of instructional supervision, theinvolvement of stakeholders were insignificant. The study also reveals statistically significantrelationship between instructional supervision, supervisors and teachers relation, stakeholdersinvolvement with quality education. Thus, to the effective practices of instructional supervision atrespective schools the researcher recommended different strategic pillars.